DYSPRAXIA AS A PSYCHOMOTOR DISORDER OF SCHOOL AGE CHILDREN - Nowak, Agata; Gnitecka, Jolanta; Romanowska-Tolloczko, Anna (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The purpose of the study was to define the epidemiology of dyspraxia among children from 6 to10 years’ age, attending grades I-III of primary schools in Wrocław, Poland. Material: the study was conducted among pupils of primary schools in Wrocław, Poland. The studied groups included 48 girls and 52 boys. The study employed Polish version of Questionnaire for the screening assessment of dyspraxia’s occurrence among children from 5 to 15 years’ age (DCDQ-PL), as well as the Coordination Test for Children (KTK). Results. After assessing the occurrence of dyspraxia among studied children, it was found out that this disorder is present in the studied group. The prevalence of dyspraxia depends on studied children’s gender; however, it is not related to their age. The results of tests, conducted with the DCDQ-PL and the KTK are consistent and confirm the observed inter-dependencies. Conclusions. Dyspraxia is a widespread psychomotor disorder, which can be diagnosed among children in the early school years. A diagnosis of a child’s development with respect to this disorder should constitute a constant element of work for teachers and educationists dealing with children at this stage of education.